Taking into account developing character of projects in nanoindustry at the stage of their planning (Путеводитель предпринимателя)
The analysis of features of nanoindustry, that allows to refer projects in this area to category of developing ones is carried out. Approach to accounting of developing character of the projects, based on allocation of zones of development is offered. Features of the project’s proactive development zone and problem of its size choice, and also the variant of the solution of this problem are described.